2012
DOI: 10.1242/jcs.091066
|View full text |Cite
|
Sign up to set email alerts
|

The novel formin FMNL3 is a cytoskeletal regulator of angiogenesis.

Abstract: SummaryThe process of angiogenesis requires endothelial cells (ECs) to undergo profound changes in shape and polarity. Although this must involve remodelling of the EC cytoskeleton, little is known about this process or the proteins that control it. We used a co-culture assay of angiogenesis to examine the cytoskeleton of ECs actively undergoing angiogenic morphogenesis. We found that elongation of ECs during angiogenesis is accompanied by stabilisation of microtubules and their alignment into parallel arrays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 51 publications
4
40
2
Order By: Relevance
“…Most strikingly, we failed to observe defects in embryos bearing mutations in genes previously shown to be required for ISV formation using MOs (Table 1; Table S3). For example, individual MO knockdowns of fmnl3 and pdgfrb cause a block in ISV sprouting (Hetheridge et al, 2012; Wiens et al, 2010). However, embryos mutant for fmnl3 um150 or pdgfrb um148 display ISV growth that is indistinguishable from wild type siblings (Figure 2A, E, F).…”
Section: Resultsmentioning
confidence: 99%
“…Most strikingly, we failed to observe defects in embryos bearing mutations in genes previously shown to be required for ISV formation using MOs (Table 1; Table S3). For example, individual MO knockdowns of fmnl3 and pdgfrb cause a block in ISV sprouting (Hetheridge et al, 2012; Wiens et al, 2010). However, embryos mutant for fmnl3 um150 or pdgfrb um148 display ISV growth that is indistinguishable from wild type siblings (Figure 2A, E, F).…”
Section: Resultsmentioning
confidence: 99%
“…This process requires complex and coordinated regulation of the endothelial cell cytoskeleton to control cell shape and polarity. In our previous work, we showed that the cytoskeletal regulator FMNL3/ FRL2 controls the alignment of stabilized microtubules during polarized endothelial cell elongation and that depletion of FMNL3 retards elongation of the intersegmental vessels in zebrafish [1]. Recent work has shown that FMNL3 is also needed for vascular lumen formation [2], a critical element of the formation of functional vessels.…”
Section: Discussionmentioning
confidence: 99%
“…ECs first undergo polarized elongation in the direction of the proangiogenic signal to become tip cells, which then guide the migration of the following stalk cells [12]. ECs depleted of FMNL3 show inhibition of this polarized elongation [1,13]. As the vessel matures, adjacent stalk cells undergo apical-basolateral polarization perpendicular to this axis to begin the process of lumen formation [14,15].…”
Section: Fmnl3 Controls Actin Cable Formation At the Early Apical Surmentioning
confidence: 99%
“…FMNL3 in contrast regulates endothelial cell elongation during angiogenic morphogenesis by microtubule alignment 96 and seems to be involved in cell motility 97 . Both, FMNL2 and FMNL3 are predominantly associated with the plasma membrane and this localization depends on their N-terminal myristoylation (Table 2).…”
Section: Fmnlmentioning
confidence: 99%